352 Did the Discontinuation of Pulse-Lavage Have A Detrimental Effect on The Quality of Hip Hemiarthroplasties Performed During the First COVID-19 Wave?. (12th October 2021) - Sharma, D; Spacey, K; Sharma, V
Abstract: Introduction: The standard of practice for performing hip hemiarthroplasty is to thoroughly wash and dry the femur with pulse-lavage. With the COVID-19 pandemic we were issued with guidance to minimise Aerosol Generating Procedures (AGPs) and discontinued the use of pulse lavage. Instead, we used a bladder syringe to wash the femoral canal. Method: We retrospectively assessed 100 post-operative radiographs following hemiarthroplasties for neck of femur fractures. We used the Barrack classification to assess the bone cement mantle which is an indicator of aseptic loosening. We assessed 50 radiographs pre-covid (using pulse lavage) and 50 radiographs during covid (without pulse lavage). Results: Pre-COVID-19, 30% of hemiarthroplasties were deemed as being 'at risk'. During COVID-19, 64% of hips were deemed as being 'at risk'. This represents an absolute increase of 34%. Conclusions: This forced service change had a detrimental effect on the quality of the bone cement mantle following hip hemiarthroplasty. We recommend following these patients up at 2 years to assess for signs of aseptic loosening. In future pandemics, we recommend carefully weighing up the dangers of using AGPs against the detriment in patient outcomes likely to be experienced.